Perancangan Alat Penentu Ukuran Pakaian Berbasis Arduino untuk UMKM pada Industri Fashion Indonesia - Gunawan, Fery; Tjandra, Sugih Sudharma (Universitas Katolik Parahyangan, 2025)
The Fashion industry in Indonesia is one of the attractive industrial sectors for the creative economy sub-sector. Based on Statistics Indonesia, the GDP at constant prices of the textile and apparel industry amounted to 34.58 Trillion in the second quarter of 2023. However, clothing sales in physical stores have decreased due to online sales. Furthermore, in physical store sales, the dressing room is limited, the clothes being tried on are unhygienic and there are restrictions on the number of trying on clothes. So, it is necessary to design a clothing sizing tool that can determine the size of clothes, maintain hygiene and reduce queuing time when trying on clothes. The design of this tool begins with conducting interviews and identifying the necessary needs. After identifying the necessary needs, proceed with designing an affinity diagram to group needs that have similarities and determine the level of importance. The results of this determination will be designed into tool specifications using the Need-metric matrix and become the basis for developing tool concepts. From these results, a prototype was designed using Arduino, ultrasonic sensor and LCD display. Testing for the tool will pay attention to the performance results of measurement accuracy and usability testing. For the usability testing method, the SUS (System Usability Scale) method is used. From the results of the study, it was found that the performance value of measurement accuracy was 75.76% and the usability testing score was obtained 68. The performance value of measurement accuracy and usability testing still needs to be improved with proposals in the form of clothing requirements during measurement and the use of more automated tools to make it easier to use.